2009
DOI: 10.1007/s00417-009-1093-7
|View full text |Cite
|
Sign up to set email alerts
|

Dose-related changes in retinal function and PKC-alpha expression in rabbits on vigabatrin medication

Abstract: In this study, VGB medication was associated, in a dose-related manner, with a decrease of ff-ERG amplitudes as well as with altered protein expression in rod bipolar cells and Müller cells, suggesting alterations of inner retinal function. The dose-related morphological and electrophysiological changes indicate a retinal pathology that may explain the constricted visual fields seen in some patients treated with VGB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…These previous studies are consistent with our observation of folds in the outer nuclear layer of the retina. Although the formation of folds is closely related to vigabatrin dose [21] and duration of light exposure [9], [11], we observed that genetic mutations could also influence fold efficiency. In this study, we tested mice that carried mutations that affected rod or cone photoreceptor signaling and observed decreased folding formation.…”
Section: Discussionmentioning
confidence: 72%
“…These previous studies are consistent with our observation of folds in the outer nuclear layer of the retina. Although the formation of folds is closely related to vigabatrin dose [21] and duration of light exposure [9], [11], we observed that genetic mutations could also influence fold efficiency. In this study, we tested mice that carried mutations that affected rod or cone photoreceptor signaling and observed decreased folding formation.…”
Section: Discussionmentioning
confidence: 72%
“…Cases have been described as symptomatic or asymptomatic, bilateral, persistent, and concentric with the nasal field often affected more extensively than the temporal field. 5,69,70 Vigabatrin-associated visual field defects have been linked to nasal quadrant retinal nerve fiber layer thinning, and this nasal attenuation may precede visual field loss. 71 Although a detailed pathophysiologic explanation for the defects remains to be elucidated, retinal damage is most often cited as the underlying defect.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…Vigabatrin has been implicated as causing reductions of specific rod and cone wave amplitudes and other changes supporting damage to the inner retina. 70 One theory regarding vigabatrin-associated visual field defects asserts that retinal toxicity may be related to coding variations in genes that transport vigabatrin into the retina. 72 Attempts to investigate correlations between duration or dosing parameters of vigabatrin and vigabatrinassociated visual field defects have typically resulted in conflicting results, some investigations have revealed associations with these parameters whereas others have not.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…2004) as well as altered expression of proteins in Müller cells (Ponjavic et al. 2004; Kjellstrom et al. 2009) and in rod bipolar cells (Kjellstrom et al.…”
Section: Introductionmentioning
confidence: 99%